The Impact Of Corruption, Country Governance Indicators And Loan Portfolio Concentration On Nonperforming Loans Of Three Selected South Asian Countries - Rehman, Abdul (2022)
The 2008 global financial crisis (GFC) has triggered a rise in nonperforming loans (NPLs) of banks around the globe, including the South Asian region. The significant increase in NPLs is worrying as it may undermine banks’ ability to grant credit and support the economic recovery of a country. The increasing trend of NPL rates and limited studies in related literature assessing NPLs in the South Asian region have motivated this study, which examines the external and internal factors that may influence the NPLs. Specifically, this study investigates the impact of control of corruption (COC), country governance (CG), and loan portfolio concentration (LPC) on nonperforming loans (NPLs) in three selected South Asian countries (Pakistan, India, and Bangladesh) for the period 2000-2017. Employing Generalized Method of Moments (GMM) dynamic panel data analysis on a sample of 81 conventional banks, the result reveals that COC has a significant and negative association with NPLs, indicating that weak control of corruption would lead to an increase in NPLs in the sample countries. As for CG, the results indicate a negative and significant relationship, suggesting that better country governance would reduce the NPLs. Using Hirschman-Herfindahl Index (HHI) for LPC, the results also show a significant negative relationship. This implies that an increase in loan portfolio concentration would decrease banks’ NPLs due to better monitoring efficiency and proper screening of loan applications. These findings provide insights to the policymakers in making strategic decisions regarding NPLs with regards to control of corruption, country governance, and loan portfolio concentration indicators.